Nonuniform Continuity of the Osmosis K(2, 2) Equation - Aiyong Chen; Yong Ding; Wentao Huang (Abstract and Applied Analysis)
The qualitative theory of differential equations is applied to the osmosis K(2, 2) equation. The parametric conditions of existence of the smooth periodic travelling wave solutions are given. We show that the solution map is not uniformly continuous by using the theory of Himonas and Misiolek. The proof relies on a construction of smooth periodic travelling waves with small amplitude.